2013
DOI: 10.1016/j.ijscr.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of female breast: A case report

Abstract: ACC is a rare malignant neoplasm. Surgical treatment is the mainstay with little role for radiotherapy and chemotherapy according to the published literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…As one of the important methods for preoperative qualitative diagnosis of breast cancer, FNAC has a similar effect to pathological examination, and its diagnostic value has been generally recognized. However, for breast adenoid cystic carcinoma, only a few case reports or a small number of sample studies describe the application of FNAC in ACC diagnosis (6,(17)(18)(19)(20)(21)(22). The diagnostic cytological findings of ACC are rarely described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the important methods for preoperative qualitative diagnosis of breast cancer, FNAC has a similar effect to pathological examination, and its diagnostic value has been generally recognized. However, for breast adenoid cystic carcinoma, only a few case reports or a small number of sample studies describe the application of FNAC in ACC diagnosis (6,(17)(18)(19)(20)(21)(22). The diagnostic cytological findings of ACC are rarely described.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic cytological findings of ACC are rarely described. There are only scattered descriptions, such as the cell smear having a single round circular hyperchromic cell, which exists in loose clusters, or the tumor cells surround the nucleus and sphere without cell homogeneous material (21,22), so there is no uniform conclusion on the diagnostic value of FNAC in ACC. Quinodoz et al (18) reported that immunocytochemistry may provide additional information on FNAC, which could be relevant not only for diagnosis but also for treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Indeed, it is a epithelial tumor that usually originates in the salivary glands, submandibular glands, and minor salivary glands. [5,6] This tumor is malignant, has low local recurrence, and rarely leads to distant metastasis, [7,8] but is strictly location-dependent. Typically, it consists of small basaloid cells with a solid cribriform pattern or epithelial cells with a tubular growth pattern in histology.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoid cystic carcinoma of the breast (ACCb) is a rare type of breast cancer, representing 0.1% of all breast tumours 2. Is more frequent in postmenopausal women with a typically triple negative phenotype (negative for oestrogen and progesterone receptors, and negative human epidermal growth factor receptor (HER2)),3 and has a histologically unique identity with biphasic pattern, consisting of laminate and pseudocystic spaces lined by myoepithelial cells, and glands lined by epithelial cells 4. This tumour has an indolent course and a good prognosis, with 5 years and 10 years overall survival of 94% and 86%, respectively,5 6 contrary to triple negative, ‘basal-like’ breast cancer.…”
Section: Introductionmentioning
confidence: 99%